Religion and marriage law : the need for reform / Russell Sandberg. - Sandberg, Russell (Bristol University Press, 2023)
Successive governments have made progressive, but ad hoc reforms to marriage law in Britain. This book provides the first accessible guide to how contemporary marriage law interacts with religion. It reveals the need for the consolidation, modernisation and reform of marriage law and sets out proposals for transformation.